El Índice de Gobierno Abierto como herramienta para mejorar la gestión pública: Un análisis para los municipios de Cundinamarca (2019)
Public management in Colombia has been through a series of reforms, configurations and modifications which have led to the deterioration of this, because unwanted situations have materialized, such as corruption, reason why initiatives such as the Open Government Index (OGI) emerges. It seeks to serve as a tool to prevent State entities from falling into these criminal acts. In the context of the above, the municipalities of the country have joined to this type of initiatives, as well as the national and departmental level, municipalities seek to fight corruption, while strengthening their public management, which is why is analyzed how the IGA has been constituted as an improvement tool for the public management in the municipalities of Cundinamarca,also identifying the process traveled until enactment, because as was evidenced, the relation between these variables is linear positive , and the incidence of IGA on management is highly significant. In this way, during the development of the investigation, it is detected that they are the public servants, the citizen participation and the technological tools which have led to the obtaining of the previously indicated results.